2006
DOI: 10.1111/j.1741-3729.2006.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Just Glad My Three Jobs Could Be During the Day”: Women and Work in a Rural Community*

Abstract: The purpose of this qualitative study was to better understand the experience of wage-earning women in the context of rural economic restructuring. An ecological and life course theoretical framework was used. Nine community leaders and 17 wage-earning women residing in a rural northern Michigan county participated in semistructured interviews, and the prevailing economic concern was low wages and lack of jobs with benefits. Women workers were affected by factors such as ties to rural family business, childcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Only on one occasion did a participant discuss women's traditional rural leisure activities such as quilting or crafts. This echoes Ames, Brosi, and Damiano-Teixeira's (2006) findings that rural women struggle to establish social supports in their community because of a lack of time due to domestic and employment responsibilities. Moreover, the women in this study and in Ames et al's study suggested that they learned to adapt and cope with social isolation and enjoy what rural life had to offer.…”
Section: Discussionsupporting
confidence: 81%
“…Only on one occasion did a participant discuss women's traditional rural leisure activities such as quilting or crafts. This echoes Ames, Brosi, and Damiano-Teixeira's (2006) findings that rural women struggle to establish social supports in their community because of a lack of time due to domestic and employment responsibilities. Moreover, the women in this study and in Ames et al's study suggested that they learned to adapt and cope with social isolation and enjoy what rural life had to offer.…”
Section: Discussionsupporting
confidence: 81%
“…Although access to and choices in the child-care subsidy system vary greatly across states, they are often limited by relatively low income-eligibility cutoffs, sizable copayments, and below-market reimbursement rates (U.S. Department of Health and Human Services, 2010). Care options in the evenings and weekends are especially limited, as are supports for combining different types of care to meet both parental employment and child development needs (e.g., part-week relative care with part-week center care; Adams & Rohacek, 2002;Ames et al, 2006). Addressing these gaps in the market might help parents select child care that meets their definitions of quality and also supports their mental health.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…The concept of elite interviews originated from the study of politics and policy-making (Dexter, 1969(Dexter, , 1970. As a result of greater emphasis on understanding decision-making processes and policy impacts and perceptions, it has subsequently become popular as a qualitative research method in the social sciences and is gaining interest amongst tourism and business management researchers, especially among graduate students (Ames, Brosi, & Damiano-Teixeira, 2006;Hall, 2011a;Lennon & Graham, 2001;Mak, 2011;Moswete & Darley, 2012;Pridham, 1999;Sharp, 2003).…”
Section: Introductionmentioning
confidence: 99%